Leadership research findings, practice, and skills - DuBrin Andrew J.
Helps you understand leadership principles and hone your own leadership skills through a thoughtful balance of essential theory and real-world applications. This title provides a strong practical foundation by introducing leaders you can relate to and reinforcing your knowledge with frequent skill-building activities.